Labradoodle : a cross between a Labrador retreiver and a Poodle - Allen, Kathy (North Mankato, Minn. : Capstone Press, 2012)
"Describes Labradoodles, their characteristics and behavior, and includes basic information on feeding, grooming, training, and healthcare"--Provided by publisher.
Includes bibliographical references (p. 31) and index.
3-6
Keywords: Labradoodle -- Juvenile literature; Labradoodle; Dogs; Labradoodles; Dogs; Dogs; Pets; Labradoodle